Influence Model Problem based Learning Against Critical Thinking Skills in Learning Thematic Integrated Class IV - Yulia Yulia; Farida F; Yuni A (International Conferences on Educational, Social Sciences and Technology)
The purpose of this study was to investigate: the effect ofmodels problem based learning to the critical thinking skills of learners in an integrated thematic learning. This research is a kind of quasi-experiment. The population is all learners in elementary Nanggalo Padang and the sample are learners class IVA and IVB as many as 52 people. The sampling technique in this research istechnique. purposive sampling Data from the research results obtained from tests of critical thinking skills. The results showed that the learning model of problem based learning affects the critical thinking skills of learners in an integrated thematic learning.